Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
The vertex form of a quadratic equation is expressed as
y = a(x - h)^2 + k
where
h and k are the x and y coordinates of the vertex of the curve formed.
a is the leading coefficient
The standard form of a quadratic equation is written as
y = ax^2 + bx + c
The given equation is
y = - x^2 + 12x - 4
By comparing the given equation with the standard form equation, we have
a = - 1
b = 12
c = - 4
We would find the x coordinate of the vertex by applying the formula,
x = - b/2a
By substituting the given values into this formula, we have
x = - 12/2 * - 1 = - 12/- 2 = 6
We would find the y coordinate of the vertex by substituting x = 6 into the given equation. We have
y = -(6)^2 + 12(6) - 4
y = - 36 + 72 - 4
y = 32
Thus,
x = h = 6
y = k = 32
a = - 1
By substituting these values into the vertex form equation, the equation in vertex form is
y = - (x - 6)^2 + 32
1) The method used was quite different. It is correct although there were some mistakes in the work.
2) Using a(x + d)^2 + e is like using a(x - h)^2 + k but the terms inside the parentheses should have been x - d
3) a (x+d)^2+ e cannot be called the 'vertex form' of a quadratic equation because the parenthses has x + d instead of x - d
4) The shorter way is the method that i used
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.